2012
DOI: 10.3171/2011.12.peds11418
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular lesions in tuberous sclerosis complex: a possible association with the caudate nucleus

Abstract: Object Tuberous sclerosis complex (TSC) can manifest with 3 principal intracranial pathological entities: cortical tubers, subependymal nodules (SENs), and subependymal giant cell astrocytomas (SEGAs). The authors analyzed the location and growth of intraventricular lesions in a large cohort of patients with TSC. Methods After institutional review board protocol approval, the authors retrospectively revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…9,10 Whether these tuberous sclerosis complex-related CNS lesions morphologically resemble the giant cells in subependymal giant cell astrocytoma is because they arise from a common origin or because they share a common genetic alteration remains controversial. 2,3,23 Finally, given the immunohistochemical evidence of mixed glioneuronal differentiation of this tumor, the classification of subependymal giant cell astrocytoma as an 'astrocytoma' may not be appropriate. 1,[8][9][10][11][12][13] In most of the subependymal giant cell astrocytomas, the giant cell feature is fairly eye-catching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Whether these tuberous sclerosis complex-related CNS lesions morphologically resemble the giant cells in subependymal giant cell astrocytoma is because they arise from a common origin or because they share a common genetic alteration remains controversial. 2,3,23 Finally, given the immunohistochemical evidence of mixed glioneuronal differentiation of this tumor, the classification of subependymal giant cell astrocytoma as an 'astrocytoma' may not be appropriate. 1,[8][9][10][11][12][13] In most of the subependymal giant cell astrocytomas, the giant cell feature is fairly eye-catching.…”
Section: Discussionmentioning
confidence: 99%
“…1 The tumor most commonly occurs in the first two decades of life and typically arises from the caudothalamic groove adjacent to the foramen of Monro. 2,3 Making the correct diagnosis of subependymal giant cell astrocytoma is highly relevant because it is one of the major diagnostic criteria for tuberous sclerosis complex. 4 In addition, due to its slowly growing nature, patients with subependymal giant cell astrocytoma are precluded from further aggressive treatment such as chemo-and radiotherapy, which are often applied to patients with higher-grade gliomas.…”
mentioning
confidence: 99%
“…Isik et al described the growth of subependymal giant cell astrocytomas in the basal ganglia of two infants with TSC . Whole‐brain mapping in individuals with TSC revealed a predominance of subependymal nodules in association with the caudate nucleus . Functionally, working memory impairments in TSC were associated with basal ganglia lesions, along with other cortical regions .…”
Section: Introductionmentioning
confidence: 96%
“…The potential for growth of these lesions has led to formal guidelines that recommend frequent periodic screening by MRI in TSC children and young adults. Further, a recent report indicated that about one third of SENs were observed to grow over a 4-year period postnatally [32]. Moreover, progressive increase in size of a SEN to a diameter >1 cm is seen in 5–10% of all children with TSC, necessitating intervention by either treatment with mTOR inhibitors, rapamycin [33] or everolimus [34], [35], or surgical removal [36], [37].…”
Section: Discussionmentioning
confidence: 99%